2022
DOI: 10.1136/bmjopen-2021-050187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the experience and mental health of university students studying in Canada and the UK: a cross-sectional study

Abstract: ObjectivesTo explore the impact of the COVID-19 pandemic on the experiences and mental health of university students.DesignA cross-sectional study consisting of an electronic survey about students’ experiences and concerns during the pandemic and the associated impact. In addition to the quantitative analysis, free-text responses were extracted and analysed using a framework technique.SettingQueen’s University in Canada and the University of Oxford in the UK.ParticipantsUndergraduate students at Queen’s Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 28 publications
11
45
0
1
Order By: Relevance
“…Similar findings have been observed in Italian undergraduate students [13], where female students reported more anxiety symptoms than males [6,[13][14][15].…”
Section: University Students' Well-being During the Pandemicsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings have been observed in Italian undergraduate students [13], where female students reported more anxiety symptoms than males [6,[13][14][15].…”
Section: University Students' Well-being During the Pandemicsupporting
confidence: 87%
“…More specifically, some studies revealed that students perceived a high degree of insecurity regarding the near future of the education process [27][28][29]. Others showed that students' psychological distress was related to the uncertainty of future career prospects [19], and increased concerns about the academic outcomes [15,27,28].…”
Section: University Students' Well-being During the Pandemicmentioning
confidence: 99%
“…Eleven items assessing the perceived impact of the pandemic and associated social distancing and remote learning, developed in collaboration with student partners, were added to the follow-up survey for Cohort 3. Students rated the impact on their university experience, including perceptions of remote learning, social relationships, leisure activities, and finances on a 5-point scale from 1 = “Very negative” to 5 = “Very positive.” 19 In addition, in both the baseline and follow-up surveys, students in Cohort 3 provided free text responses to the open-ended question “ Are there any other significant impacts related to the COVID-19 pandemic on your mental health, wellbeing, or education that you would like to comment on? ”…”
Section: Methodsmentioning
confidence: 99%
“…From this moment, the normal course of medical study changed diametrically. Difficulties related to the reorganization of academic science, as well as direct contact with patients during classes in clinical subjects, where the potential risk of COVID-19 infection was much higher than in other conditions, the need to exercise particular caution, wear protective clothing, and the constantly changing guidelines for procedures were factors generating tension and affecting health and life satisfaction [ 17 , 18 ]. Effective coping with stress in this period could be of particular importance for minimizing its negative effects, also in the long term [ 19 ].…”
Section: Introductionmentioning
confidence: 99%